DNA methylation of HOX genes and its clinical implications in cancer - Xin Hu; Yong Wang; Xiaoyu Zhang; Chensheng Li; Xikun Zhang; Dongxia Yang; Yuanyuan Liu; Lianlian Li (Elsevier, 2023)
Homeobox (HOX) genes encode highly conserved transcription factors that play vital roles in embryonic development. DNA methylation is a pivotal regulatory epigenetic signaling mark responsible for regulating gene expression. Abnormal DNA methylation is largely associated with the aberrant expression of HOX genes, which is implicated in a broad range of human diseases, including cancer. Numerous studies have clarified the mechanisms of DNA methylation in both physiological and pathological processes. In this review, we focus on how DNA methylation regulates HOX genes and briefly discuss drug development approaches targeting these mechanisms.